Biopolymers and Biomaterials - Padinjakkara, Aneesa; Thankappan, Aparna; Souza, Jr., Fernando Gomes; Thomas, Sabu; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
Biopolymers are attracting immense attention of late because of their diverse applications that can address growing environmental concerns and energy demands. The development of various biomaterials creates significant advancements in the medical field as well, and many biopolymers are used for the fabrication of biomaterials. Together, biopolymers and biomaterials create great potential for new materials, applications, and uses. This new volume, Biopolymers and Biomaterials, covers the science and application of biopolymers and biomaterials. It presents an array of different studies on biopolymers and biomaterials, along with their results, interpretation, and the conclusions arrived at through investigations. It includes biopolymer synthesis, their characterizations, and their potential applications. The book begins with an explanation of the different biopolymers used in the textile industry, their advantages and disadvantages, and their applications.
Biopolymers in Textile Industry -- Asim Kumar Roy Choudhury -- Importance of Wood Preservation: An Indian Overview -- Aparna Kalawate -- Cashew Nut Shell Liquid-Based Advanced Functional Materials -- Shabnam Khan, Laxmi, Hina Zafar, Eram Sharmin, Fahmina Zafar, and Nahid Nishat -- Synthesis and Characterization of Cashew Nut Shell Liquid (CNSL) Matrix Compositions for Composites Applications -- A. V. Sawant, A. R. Takalkar, and K. Padmanabhan -- Synthetic Approach for Polyurethane from Renewable Material (Cashew Nut Husk Tannin) -- A. J. Sunija and S. Siva Ilango -- Recycling of Textile Mill (Cellulosic) Waste Into Carboxymethyl Cellulose (CMC) for Textile Printing -- Javed Sheikh and V. D. Gotmare -- Sustainable Noise Control Materials Based on Bamboo/Unsaturated Polyester Composites: Analysis of Factors Affecting the Sound Absorption Coefficients -- Elammaran Jayamani, Sinin Hamdan, and Muhammad Khusairy Bin Bakri -- Morphological and Dynamic Mechanical Properties of Chemically Treated Bauhinia racemosa/Glass Fiber Polymer Composites -- J. Ronald Aseer, K. Sankaranarayasamy, P. Jeyabalan, and Priya K. Dasan -- Optimization of Plasma Modification for Low-Temperature Dyeing of Silk Fabric -- M. D. Teli, Pintu Pandit, and Kartick K. Samanta -- Partial Replacement of Carbon Black by Rice Hulls and Soy Short Fibers as Fillers in Natural Rubber Composites: Effect on Mechanical Properties -- Ajay Vasudeo Rane, Krishnan Kanny, V. K. Abitha, and Sabu Thomas -- Bio-Resins and Bio-Plastics Synthesized from Agricultural Products for Novel Applications: The Indian Projection -- K. Padmanabhan -- Mechanical Properties of Sandwich Composites Made Using Natural Fibers and Glass Fiber Mat -- R. Gopinath, K. Ganesan, and R. Poopathi -- Fabrication and Characterization of Composite Membrane of Crosslinked Polyvinyl Alcohol and Hydroxyapatite for Tissue Engineering -- Debapriya Banerjee, Anindya Haldar, and Piyali Basak -- In-Situ Nanosilver Immobilized CS/OCMC Blend Dressings for Wound Management -- Shakeel Ahmed and Saiqa Ikram -- Synthesis and Characterization of Biodegradable Polyether Urethane for the Purpose of Controlled Release of Antibiotics -- Anindya Haldar, Debapriya Banerjee, Nandan Kumar Jana, and Piyali Basak -- Biodegradation Study of Polyurethane for Therapeutic Applications -- Sohini Sen, Anindya Haldar, Nandan Kumar Jana, and Piyali Basak -- Microscopy and Spectroscopy Characterization of Ecofriendly Composites and Nanocomposites -- Raghvendra Kumar Mishra, V. R. Remya, Mufeeda Kandatharavintakath, Sabu Thomas, and Nandakumar Kalarikkal -- Nanotechnology for Smart and Intelligent Food Packaging -- Ajith James Jose and Muthukaruppan Alagar.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Material Science; Biopolymers; Electronic books